2020
DOI: 10.3389/fneur.2020.00325
|View full text |Cite
|
Sign up to set email alerts
|

Admission Levels of Total Tau and β-Amyloid Isoforms 1–40 and 1–42 in Predicting the Outcome of Mild Traumatic Brain Injury

Abstract: Background: The purpose of this study was to investigate if admission levels of total tau (T-tau) and β-amyloid isoforms 1-40 (Aβ40) and 1-42 (Aβ42) could predict clinical outcome in patients with mild traumatic brain injury (mTBI). Methods: A total of 105 patients with mTBI [Glasgow Coma Scale (GCS) ≥ 13] recruited in Turku University Hospital, Turku, Finland were included in this study. Blood samples were drawn within 24 h of admission for analysis of plasma T-tau, Aβ40, and Aβ42. Patients were divided into … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 52 publications
(73 reference statements)
0
13
0
Order By: Relevance
“…On the other hand, Thelin et al, (2019) demonstrated that tau protein provided a highly significant predictor of outcome and mortality following TBI. Also, Hossain et al, (2020) revealed that the results of patients with mild TBI were substantially connected with the amounts of tau protein present at the time of admission. Therefore, tau protein may be able to predict the sequelae of mild TBI.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, Thelin et al, (2019) demonstrated that tau protein provided a highly significant predictor of outcome and mortality following TBI. Also, Hossain et al, (2020) revealed that the results of patients with mild TBI were substantially connected with the amounts of tau protein present at the time of admission. Therefore, tau protein may be able to predict the sequelae of mild TBI.…”
Section: Discussionmentioning
confidence: 97%
“…43 In patients with mTBI, it has been observed that though T-tau levels are correlated with outcome, they are not able to predict full recovery. 42 Biomarker panels have also shown promise in outcome prediction as shown earlier in case of combining GFAP and UCH-L1. 64 In a study including multiple biomarkers, a combination of GFAP, heart fatty acid binding protein (H-FABP) and NF-L yielded a specificity of 40% when sensitivity was set at 95%-100% in predicting complete recovery in patients with mild TBI.…”
Section: Current Evidencementioning
confidence: 90%
“…The P‐tau levels and P‐tau/T‐tau ratio outperformed the T‐tau level in discriminating patients with favourable and unfavourable outcome in patients with moderate to severe TBI 43 . In patients with mTBI, it has been observed that though T‐tau levels are correlated with outcome, they are not able to predict full recovery 42 …”
Section: Biomarkers In Outcome Prediction and Late Assessment Of Trau...mentioning
confidence: 99%
See 1 more Smart Citation
“…Several proteins, such as glial fibrillary acidic protein (GFAP), S100 astroglial calcium-binding protein B (S100B), cleaved-tau protein, ubiquitin carboxy-terminal hydrolase L1 (UCH-L1), and neurofilament light polypeptide, , have been identified as potential fluid biomarkers of CNS injuries . While clinical assessments and imaging techniques are used to diagnose many CNS injuries, the detection of these fluid biomarkers may provide an equally accurate and objective assessment, complementing currently used clinical assessments. ,,, In recent years, astrocytes have become a major focus of CNS injuries due to their pivotal roles in the neurovascular unit, including blood–brain barrier (BBB) function, cerebrovascular regulation, and metabolism.…”
Section: Introductionmentioning
confidence: 99%